EDUCATIONAL IMPACTS AND INTERACTIONS CREATED BY SOCIAL MEDIA INFLUENCERS REGARDING ACCESSIBILITY IN THE AREA OF COMMUNICATION - Tomova, Ekaterina (Student Niepełnosprawny. Szkice i Rozprawy, 2021)
The article presents the results of research related to possibilities of moral and intercultural education contained in social networks and accessibility in the area of communication. The aim of the study is to identify and describe the impact of influencers on adolescents in regard to accessibility to information and communication. A software solution was used in order to obtain samples for the analysis of multiple posts published by different individuals in various social networks. The results indicate that opportunities for an effective process of education concerning the aforementioned elements can be observed if the content published by influencers is compliant with certain factors. Some of those factors are as follows: the posts should describe personal examples to which people can relate or can perceive in order to comprehend the challenges connected to accessibility in a better way; the content should comprise explanations that clarify  situations and issues, providing information and raising awareness; the followers and the influencers should encourage discussions on these topics, ensuring that decisions should be made and solutions should be found on the matter of accessibility in the area of communication.